Serenity in the crisis: Seneca’s Epistle 24 - Renata Cazarini de Freitas (Cadernos de Letras da UFF, 2018)
In the imminence of a critical situation, there is no reason to anticipate suffering, warns Seneca in Epistle 24 of the voluminous correspondence of Stoic ethics addressed to his friend Lucilius. The sophistication of the author in the treatment of the philosophical matter adapted to the epistolographic genre comes to the fore in the use of the exempla and in the direct interlocution with death. This is an epistle that reveals a tense and unpredictable political context.